Exploring Religious Moderation Practices in The Faculty of Medicine and Health Sciences at Mataram University - Lenny Herlina; Agus Kurnia; Arif Nasrullah (Universitas Islam Negeri (UIN) Mataram, 2024)
This study aims to describe and understand the practices of religious moderation among students at the Faculty of Medicine and Health Sciences, Mataram University. Employing a qualitative, descriptive-analytical approach, data was collected through observation, interviews, and documentation. The study participants included students, faculty advisors, and the dean’s office staff. Findings revealed inclusive and tolerant student activities, both within religious-based organizations and interfaith initiatives, with full support from the faculty. The faculty is committed to instilling moderate values by fostering mutual respect, rejecting primordialism, upholding the rule of law, promoting nationalism, and resolving conflicts in an accommodative manner. The implementation of religious moderation practices among FKIK UNRAM students has been successful, evidenced by inclusive and tolerant activities, along with strong institutional support.